1993
DOI: 10.1111/j.1365-2958.1993.tb01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium smegmatis RNA polymerase: DNA supercoiling, action of rifampicin and mechanism of rifampicin resistance

Abstract: We have isolated RNA polymerase from Mycobacterium smegmatis and established conditions for specific transcription initiation in vitro. The M. smegmatis enzyme has a strong dependence on supercoiling of the DNA substrate for transcription from mycobacterial promoters. We also show that RNA polymerase is the target for rifampicin, and that this antibiotic specifically inhibits the transition from synthesis of short oligoribonucleotides to full-length transcripts. RNA polymerase isolated from a rifampicin-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 28 publications
8
60
0
2
Order By: Relevance
“…The experiment was therefore performed using RNA isolated from M. smegmatis cells harbouring various katG promoter clones. The determination of transcription start sites for M. tuberculosis genes, using this heterologous host, has been shown to correlate well with results obtained from native mRNA transcripts (Levin & Hatfull, 1993 ;Dhandayuthapani et al, 1997 ;Movahedzadeh et al, 1997), and has successfully been used as a substitute in many cases (Murray et al, 1992 ;Kremer et al, 1995 ;Nesbit et al, 1995).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The experiment was therefore performed using RNA isolated from M. smegmatis cells harbouring various katG promoter clones. The determination of transcription start sites for M. tuberculosis genes, using this heterologous host, has been shown to correlate well with results obtained from native mRNA transcripts (Levin & Hatfull, 1993 ;Dhandayuthapani et al, 1997 ;Movahedzadeh et al, 1997), and has successfully been used as a substitute in many cases (Murray et al, 1992 ;Kremer et al, 1995 ;Nesbit et al, 1995).…”
Section: Discussionsupporting
confidence: 54%
“…The surrogate host of choice is Mycobacterium smegmatis because of its non-pathogenicity and rapid growth. The M. smegmatis RNA polymerase has been purified and used for transcription initiation in vitro (Levin & Hatfull, 1993). The major form of this enzyme has marked conservation with that of E. coli (Predich et al, 1995), which suggests some common mechanisms of transcription initiation.…”
Section: Introductionmentioning
confidence: 99%
“…According to evaluation based on CLSI standards for slow-growing bacteria, these two isolates should be considered intermediately susceptible. On the other hand, in this study we have characterized the whole rpoB gene, recognized to be the RIF antibiotic target in prokaryotes (16,17,19), of all our isolates, and these two isolates carried only the B. melitensis biovar 3 molecular marker (M1249I). We can, therefore, assert that all isolates investigated were found to be sensitive to RIF and, in general, to all tested antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Because rifampin resistance-conferring mutations in rpoB have also been observed in nontuberculous Mycobacteria species (Honoré and Cole 1993;Levin and Hatfull 1993;Musser 1995) and because the use of 16S genotyping has proven problematic in speciating some mycobacteria (Fox et al 1992), the rpoB oligonucleotide array and conventional dideoxynucleotide sequencing were used to analyze sequence diversity within and between members of the mycobacterial genus. Among the 10 Mycobacterium species studied, analysis of the 705 nucleotides of the rpoB gene revealed that intraspecies variation was smallest within M. tuberculosis, M. xenopi, and M. kansasii species and greatest within M. gordonae, M. fortuitum, and M. smegmatis species.…”
Section: Discussionmentioning
confidence: 99%